Performance Evaluation of AODV and MDORA Protocols in Different Cases of Vehicles Movement - ganim, ahmed; Mohammed, Dania (International Journal of Integrated Engineering, 2019)
Among the most important topics that have been under discussion are how to manage traffic at intersections and how to maintain road safety. Vehicular Network (VANETs) is one of the most important solutions to solve this problem. And to routing packets between vehicles, many protocols have been proposed. And from this protocols are the MDORA protocol and AODV protocol. This work provides a comparison between the two MDORA and AODV protocols in two cases at variable speed of vehicles, the first in the case of vehicles movement in several directions, and the second in the case of vehicles movement in one direction. The comparison results for the first case the MDORA protocol were worse than the AODV protocol in terms of (E2E end to end delay, PDR packet delivery ratio, communication overhead), while the comparison results in the second case of the MDORA protocol were better than the AODV protocol in terms of (E2E end to end delay , PDR packet delivery ratio, communication overhead), because in the MDORA algorithm there was a condition is choose the vehicles that moved with the same direction when to routing packets to the destination vehicle ,so negative results appeared in the first case.